An Identification of Porphyry Deposit Based On Time Domain Induced Polarization Data Analysis in The Papua Region - Y Yatini; Gilvandro Rumahorbo; Sutarto Sutarto (Journal of Engineering and Scientific Research, 2023)
Papua is one of the islands in Indonesia which has an abundance of economic metal mineralization in Indonesia. The types of mineralized deposits on the island of Papua are porphyry, skarn and epithermal, where porphyry deposits are identified in the study area, which were identified early by geological conditions. The geophysical approach is carried out using Time Domain Induced Polarization data analysis, TDIP measurements are carried out on an area of 2.24km2, with a total of 3 line oriented southeast-northwest along 3 km. Based on TDIP data analysis, there’s low resistivity anomaly correlates with high chargeability which is interpreted as a Potassic body at an elevation of 500m, while above it there are Serisitic-Clay-Chlorite and Serisitic-Clay-Pyrite alterations with high metal sulfide content up to 1100m elevation.